2022
DOI: 10.3126/nh.v16i1.44968
|View full text |Cite
|
Sign up to set email alerts
|

Vegetative Propagation of Eureka Seedless Lemon (Citrus limon L.Cv Eureka seedless) using Different Types of Stem Cutting and Concentrations of Indole-3-Butyric Acid in Winter

Abstract: Citrus can be propagated successfully through stem cutting. However, success of the propagation is depends on various internal as well as external factors.  The 2*7 factorial Randomized Complete Block Design (RCBD) experiment was conducted at the Institute of Agriculture and Animal Sciences, Paklihawa Campus, Rupandehi, Nepal from 22 November 2019 to 5 March 2020 to assess the interaction effect of types of stem cuttings and indole 3 butyric acid (IBA) concentrations on the vegetative propagation of Eureka see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…According to the result, the maximum sprouting percentage was observed at 4000 ppm IBA concentration. Along with that, the days for sprouting were about 33.16 [23].…”
Section: Effect On the Day Required For Sproutingmentioning
confidence: 84%
See 1 more Smart Citation
“…According to the result, the maximum sprouting percentage was observed at 4000 ppm IBA concentration. Along with that, the days for sprouting were about 33.16 [23].…”
Section: Effect On the Day Required For Sproutingmentioning
confidence: 84%
“…The study of Gnawali et al, (2022) demonstrates the vegetative growth of Citrus limon in the treatment of IBA in various doses. An experiment was designed to observe sprouting percentage, day of sprouting, length of leaves and shoots, etc.…”
Section: Effect On the Day Required For Sproutingmentioning
confidence: 99%
“…Plant growth regulator is used for transplant survival, establishment, and tuber production of potato by shoot-tip cutting. However, effective exogenous auxin treatments for successful transplant survival, establishment, and tuber production depend on many factors including type of auxin applied, type of variety treated, and number of nodes on the cutting (cutting length), the age of the mother plant when the cuttings are taken and concentration of exogenous auxin applied (Gnawali et al, 2022). Yasser et al ( 2018) reported that the application of 6000 ppm of IBA gave best growth and yield of potato.…”
Section: Introductionmentioning
confidence: 99%